ALK F1174S mutation impairs ALK kinase activity in EML4-ALK variant 1 and sensitizes EML4-ALK variant 3 to crizotinib - Guan, Jikui; Chuang, Tzu-Po; Vikström, Anders; Palmer, Ruth H.; Hallberg, Bengt (Frontiers in Oncology, 2024)
Objective: To assess the influence of F1174S mutation on kinase activity and drug sensitivity of the echinoderm microtubule-associated protein-like 4 (EML4) and anaplastic lymphoma kinase (ALK) fusion (EML4-ALK) variants 1 and 3.We constructed mammalian expression plasmids of both wildtype and F1174 mutant EML4-ALK variants 1 and 3, and then characterized them with cell models by performing immunoblotting, neurite outgrowth assay, focus formation assay as well as protein stability assay. Drug sensitivity to ALK tyrosine kinase inhibitors was also compared between wildtype and F1174 mutant EML4-ALK fusions. In addition, we characterized the effect of different F1174 kinase domain mutations in the context of EML4-ALK fusions.In contrast to the oncogenic ALK-F1174S mutation that has been reported to be activating in the context of full-length ALK in neuroblastoma, EML4-ALK (F1174S) variant 1 exhibits impaired kinase activity leading to loss of oncogenicity. Furthermore, unlike the previously reported F1174C/L/V mutations, mutation of F1174 to S sensitizes EML4-ALK variants 3a and 3b to crizotinib.These findings highlight the complexity of drug selection when treating patients harboring resistance mutations and suggest that the F1174S mutation in EML4-ALK variant 1 is likely not a potent oncogenic driver. Additional oncogenic driver or other resistance mechanisms should be considered in the case of EML4-ALK variant 1 with F1174S mutation.